2013
DOI: 10.1007/978-1-62703-580-4_20
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiling Using DNA Microarrays

Abstract: In Arabidopsis research, microarrays have typically been employed for the measurement of gene expression under different conditions. Microarray analysis is often used to analyze the effects of the expression of wild-type genes (control) versus mutants, the effects of varying environmental conditions, and the effects of hormones. In addition, microarray analysis is used to analyze differences in gene expression between growth stages and tissues. Other array applications include comparative genomic hybridization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Raw data were analyzed using GeneSpring GX software, version 12.0 (Agilent Technologies). Expression log ratios and the Benjamini and Hochberg FDR P values were calculated using GeneSpring GX (Maruyama et al, 2014). The microarray design and data were deposited at MIAMExpress (accession nos.…”
Section: Microarray Analysismentioning
confidence: 99%
“…Raw data were analyzed using GeneSpring GX software, version 12.0 (Agilent Technologies). Expression log ratios and the Benjamini and Hochberg FDR P values were calculated using GeneSpring GX (Maruyama et al, 2014). The microarray design and data were deposited at MIAMExpress (accession nos.…”
Section: Microarray Analysismentioning
confidence: 99%
“…DNA microarray is one of the most popular technologies for gene expression profiling used in the past 15 years [ 28 , 42 , 46 , 50 , 68 ]. In this study we presented the development and the validation of the microarray CAZyChip dedicated to analyze the bacterial glycoside hydrolase expression.…”
Section: Discussionmentioning
confidence: 99%
“…DNA microarrays are widely used to profile gene expression and represent a relevant tool to study expression of key enzymes and monitor physiological changes of pure cultures or microbial communities [ 12 , 18 , 28 , 42 , 46 , 50 , 68 ]. This approach can also be useful to link microbial diversity to ecosystem processes and functions [ 22 , 29 , 67 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the past few decades, increasing evidence has confirmed that microarrays and bioinformatics analyses could be performed to evaluate potential biomarkers in multiple diseases at molecular levels . Gene expression profiling (GEP) is an effective way to identify important molecules and mechanistic pathways . GEP has been carried out to compare the differently expressed genes between ALT‐negative and ALK‐positive ALCL samples, improving the diagnosis and classification of ALCLs.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Gene expression profiling (GEP) is an effective way to identify important molecules and mechanistic pathways. 10 GEP has been carried out to compare the differently expressed genes between ALT-negative and ALK-positive ALCL samples, 11 improving the diagnosis and classification of ALCLs. Super-enhancers were found in multiple adult T-cell leukemia/lymphoma (ATLL) but no expression in normal mature T cells by GFP, implicating involvement of those genes in ATLL pathogenesis.…”
mentioning
confidence: 99%